Outcome of refractory and relapsed acute myeloid leukemia in children treated during 2005-2011 – experience of the Polish Pediatric Leukemia/Lymphoma Study Group (PPLLSG) - Skalska-Sadowska, Jolanta; Wachowiak, Jacek; Zając-Spychała, Olga; Niewiadomska-Wojnałowicz, Izabela; Januszkiewicz-Lewandowska, Danuta; Balwierz, Walentyna; Pawińska-Wąsikowska, Katarzyna; Goździk, Jolanta; Chybicka, Alicja; Potocka, Kinga; Krawczuk-Rybak, Maryna; Muszyńska-Rosłan, Katarzyna; et al. (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Recent studies showed relatively better outcome for children with refractory (refAML) and relapsed acute myeloid leukemia (relAML). Treatment of these patients has not been unified within Polish Pediatric Leukemia/Lymphoma Study Group (PPLLSG) so far. The goal of this study is to analyze the results of this therapy performed between 2005–2011. Material and methods : The outcome data of 16 patients with refAML and 62 with relAML were analyzed retrospectively. Reinduction was usually based on idarubicine, fludarabine and cytarabine with allogenic hematopoietic stem cell transplant (alloHSCT) in 5 refAML and 30 relAML children. Results: Seventy seven percent relAML patients entered second complete remission (CR2). Five-year OS and disease-free survival (DFS) were estimated at 16% and 30%. The outcome for patients after alloHSCT in CR2 (63%) was better than that of those not transplanted (36%) with 5-year OS of 34% vs. 2-year of 7% and 5-year DFS of 40% vs. 12.5%. Second complete remission achievement and alloHSCT were the most significant predictors of better prognosis (p = 0.000 and p = 0.024). The outcome of refAML children was significantly worse than relAML with first remission (CR1) rate of 33%, OS and DFS of 25% at 3 years and 53% at 2 years, respectively. All survivors of refAML were treated with alloHSCT after CR1. Conclusions : The uniform reinduction regimen of the documented efficacy and subsequent alloHSCT in remission is needed to improve the outcome for ref/relAML children treated within PPLLSG. The focus should be on the future risk-directed both front and second line AML therapy.